Fabrication and characterisation of B-H-G fiber with teak wood particles reinforced hybrid composite - ., Deenadayalan; Sivakuma, S; Vishnuvardhan, R; Sathish Kumar, R (International Journal of Engineering and Technology, 2018)
In recent years, natural fiber based hybrid composite materials have replaced many conventional metals and synthetic resin composites in many applications. The natural fibers serve better in the present unsustainable environment due to their properties. The waste wood particles from saw mill can also be added as reinforcement element in the matrix. Hence, to enhance the strength of the composite, fine teak wooden particles are mixed with the composite matrix material. The aim of this work is to develop hybrid fiber reinforced composite with waste teak wooden particles with optimum properties. Therefore it can replace the existing synthetic fiber reinforced composite material for a suitable application. In this work, epoxy resin has been reinforced with the hybrid fibers (Banana, Hemp and E-glass) to develop fiber reinforced plastic (FRP) with a weight ratio of 1:2 hand lay-up technique. The thickness of the composite specimen is obtained by laying up layer of fiber and matrix with wood particle. An experimental investigation of tensile, flexural, impact strength and water absorption capacity of the B-H-G Teak wood particle hybrid composite laminates have been carried out according to the ASTM standard of the composite laminates.Â Â